New immunomodulatory treatment protocol for canine leishmaniosis reduces parasitemia and proteinuria. - Guadalupe Miró; Sergi Segarra; José Joaquín Cerón; Lluís Ferrer; Laia Solano-Gallego; Laia Montell; Ester Costa; Joan Teichenne; Roger Mariné-Casadó; GALILEI trial Group; Xavier Roura (PLoS Neglected Tropical Diseases)
The current standard treatment for canine leishmaniosis (CanL), N-methylglucamine antimoniate (MGA) given with allopurinol, is not fully effective and may cause adverse effects and drug resistance. In vitro and in vivo studies have shown that nucleotides, administered alone or with AHCC, offer benefits in the treatment of CanL. This study examines the effects of a new immunomodulatory treatment protocol in which dietary nucleotides and AHCC are added to the recommended standard treatment. Out of 160 sick dogs with naturally occurring clinical leishmaniosis recruited, 97 were randomized to a supplement (n = 47) or control (n = 50) group. All dogs received an initial 28-day course of MGA and 365-day course of allopurinol. From day 0 to day 730, dogs in the control group additionally received a placebo, while dogs in the supplement group received Impromune (Bioiberica S.A.U., Esplugues de Llobregat, Spain), an oral supplement providing 32 mg/kg nucleotides and 17 mg/kg AHCC daily. After 2 years, five dogs had relapsed in the supplement group (18.5%) while seven did so in the control group (22.6%). Over time, animals in both groups showed significant improvements in body weight, LeishVet clinical stage, clinical score, and anti-Leishmania antibodies. Adding the supplement to the standard protocol resulted in further significant improvements, namely in reducing the parasite load and urinary protein/creatinine ratio, improving IRIS stage, lowering serum creatinine levels on day 30, deceasing urine turbidity on day 365, and improving weight gain on day 545. The daily intake of the supplement over two years proved safe and well tolerated. Our study confirms the efficacy of the recommended standard treatment for CanL, but also reveals that by adding Impromune additional benefits are obtained, especially reduced parasitemia and improved renal function.